2022
DOI: 10.1021/acs.jcim.2c01028
|View full text |Cite
|
Sign up to set email alerts
|

Early Steps in C-Type Inactivation of the hERG Potassium Channel

Abstract: Fast C-type inactivation confers distinctive functional properties to the hERG potassium channel, and its association to inherited and acquired cardiac arrythmias makes the study of the inactivation mechanism of hERG at the atomic detail of paramount importance. At present, two models have been proposed to describe C-type inactivation in K+-channels. Experimental data and computational work on the bacterial KcsA channel support the hypothesis that C-type inactivation results from a closure of the selectivity f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
2
6
0
Order By: Relevance
“…Previously, a similar effect was noticed by Jensen & Shaw in their remarkable in silico simulation of voltage gating of a K v [35]. SF reveals to be a surprisingly stable structure, deviating from the almost ideal square- antiprismatic geometry only upon C-type inactivation (our unpublished analysis), which, however, is likely to occur in hERG [55,56]. It is not clear whether this structural alteration would affect BeKm-1 binding, since the toxin interacts with the regions above the SF, although it is assumed to interfere with the binding of some small molecules [57].…”
Section: Discussionsupporting
confidence: 83%
“…Previously, a similar effect was noticed by Jensen & Shaw in their remarkable in silico simulation of voltage gating of a K v [35]. SF reveals to be a surprisingly stable structure, deviating from the almost ideal square- antiprismatic geometry only upon C-type inactivation (our unpublished analysis), which, however, is likely to occur in hERG [55,56]. It is not clear whether this structural alteration would affect BeKm-1 binding, since the toxin interacts with the regions above the SF, although it is assumed to interfere with the binding of some small molecules [57].…”
Section: Discussionsupporting
confidence: 83%
“…The published structures for the “inactivated” state of Shaker, however, are based on mutant structures, rather than changes in K + concentration. In a recent MD simulation study of HERG, Pettini and colleagues showed that mutants that promoted inactivation led to widening of the extracellular entrance of the channel, but less prominent than what was seen in Shaker 25 . In our cryo-EM structures we observed a small dilatation of the upper filter, in both the high-K and low-K structures ( Supplementary Fig S5 ).…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that such a subtle structural change was consistent with the rapidity of inactivation in HERG 22 . Conversely, Molecular dynamics (MD) simulation studies of the WT HERG structure suggested that the transition from conducting to non-conducting selectivity filter structures could involve asymmetric buckling of the selectivity filter 23,24 , and/or dilation of the upper filter 23,25 . An alternative explanation for the similarity of the WT and S631A HERG structures is that they both represent subtly different conductive state structures 23,26,27 .…”
Section: Introductionmentioning
confidence: 99%
“…Having shown that ICA-105574 can rescue the activity of G628S and A561V but not that of L779P in vitro , we set out to understand the molecular determinants of this rescue mechanism using MD simulations. Previous work on the hERG channel showed rapid inactivation on the ns time scale for the wild-type protein, making it difficult to accumulate extensive statistics on the conformational dynamics of the hERG active state (16, 17, 37). Here we started with a known cryo-EM structure (PDB ID: 5VA2) determined in the active state for the wild type ( Figure 3A ), including the PAS domain (15), in a POPC bilayer with 200 mM salt concentration (KCl) and applied transmembrane voltage ranging from ∼650 mV to ∼750 mV.…”
Section: Resultsmentioning
confidence: 99%